Determining collagen distribution in articular cartilage using contrast-enhanced micro-computed tomography. Issue 9 (September 2015) - Nieminen, H.J.; Ylitalo, T.; Karhula, S.; Suuronen, J.-P.; Kauppinen, S.; Serimaa, R.; Hæggström, E.; Pritzker, K.P.H.; Valkealahti, M.; Lehenkari, P.; Finnilä, M.; Saarakkala, S.
Summary: Objective: Collagen distribution within articular cartilage (AC) is typically evaluated from histological sections, e.g., using collagen staining and light microscopy (LM). Unfortunately, all techniques based on histological sections are time-consuming, destructive, and without extraordinary effort, limited to two dimensions. This study investigates whether phosphotungstic acid (PTA) and phosphomolybdic acid (PMA), two collagen-specific markers and X-ray absorbers, could (1) produce contrast for AC X-ray imaging or (2) be used to detect collagen distribution within AC. Method: We labeled equine AC samples with PTA or PMA and imaged them with micro-computed tomography (micro-CT) at pre-defined time points 0, 18, 36, 54, 72, 90, 180, 270 h during staining. The micro-CT image intensity was compared with collagen distributions obtained with a reference technique, i.e., Fourier-transform infrared imaging (FTIRI). The labeling time and contrast agent producing highest association (Pearson correlation, Bland–Altman analysis) between FTIRI collagen distribution and micro-CT -determined PTA distribution was selected for human AC. Results: Both, PTA and PMA labeling permitted visualization of AC features using micro-CT in non-calcified cartilage. After labeling the samples for 36 h in PTA, the spatial distribution of X-ray attenuation correlated highly with the collagen distribution determined by FTIRI in both equine (mean ± S.D. of the Pearson correlation coefficients, r  = 0.96 ± 0.03, n  = 12) and human AC ( r  = 0.82 ± 0.15, n  = 4). Conclusions: PTA-induced X-ray attenuation is a potential marker for non-destructive detection of AC collagen distributions in 3D. This approach opens new possibilities in development of non-destructive 3D histopathological techniques for characterization of OA.